Factors Affecting AI Adoption for PHBS in High School Settings in Deli Serdang Regency - Frisca Ayu Arizta; Ismail Efendy; Indah Anggraini (Universitas Ibn Khaldun Bogor, 2026)
The rapid development of Artificial Intelligence (AI) has created new opportunities in health education, particularly among adolescents who are highly engaged with digital technology. However, the implementation of Clean and Healthy Living Behavior (PHBS) among students remains suboptimal, and the use of AI as an educational medium is still limited. This study aimed to analyze factors influencing the use of AI technology as an educational medium in improving the implementation of PHBS among students. A quantitative study with an analytic cross-sectional design was conducted among 72 Grade XI students selected using cluster random sampling from a total population of 260 students. Data were collected using structured questionnaires and analyzed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses with a significance level of p < 0.05. The majority of students had poor knowledge (80.6%), negative attitudes (73.6%), and did not implement PHBS (65.3%). Bivariate analysis showed that knowledge, attitude, facilities, teacher support, and parental support were significantly associated with PHBS (p < 0.05). Multivariate analysis identified knowledge (p < 0.001; OR = 60.496), attitude (p = 0.002; OR = 27.196), and teacher support (p = 0.041; OR = 5.875) as significant predictors, with knowledge being the most dominant factor. The implementation of PHBS among students is influenced by both individual and environmental factors, with knowledge as the strongest determinant. The integration of AI-based educational tools, supported by teacher involvement, has strong potential to improve students’ health behavior.